Terrorism, Militancy and Insurrection in Nigeria: The Inevitability of Adopting Appropriate Conflict Management Strategies - Ikporukpo, Iyabrade; Eremie, Vincent Tam (EBSU Journal of Social Sciences and Humanities, 2021)
The acts of terrorism, militancy and insurrection in Nigeria have assumed a frightening dimension and these have continually threatened the country's stability, prosperity and peace for its people. Attempts have been made by scholars and layman over the years to offer their views and sometimes contradictory opinions on the origin, violent nature and justification of these acts. This paper critically examines the emergence of the various groups perpetrating these acts, their modus-operadi and justification for their acts. We relied on the secondary source of data collection and using the structural functionalism approach as its theoretical framework, the paper posits that the state has demonstrated lack of capacity through its reactive/palliative crises management strategies to tackle the menace of these groups. The paper further argued that the seemingly helplessness of the state has resulted in some of these groups seeking for self survival and sustenance techniques. It is the position of this paper that unless different crises management strategies are adopted, the corporate existence of the Nigerian state is not guaranteed. The paper made implementable recommendations.